Гетьманські агенти як канал отримання гетьманом Лівобережної України І. Самойловичем відомостей про стан справ у Речі Посполитій (1672-1687 рр.) - Алмазов, О. (Сiверянський лiтопис, 2015)
Стаття присвячена питанню про роль агентів гетьмана Лівобережної України Івана Самойловича в процесі збору відомостей про стан справ у Речі Посполитій у добу його гетьманства (1672–1687 рр.). У роботі аналізуються склад агентів, методи їхньої роботи, коло питань, що цікавили гетьмана та його оточення, а також вірогідність свідчень інформаторів. Статья посвящена вопросу о роли агентов гетмана Левобережной Украины Ивана Самойловича в процессе сбора сведений о состоянии дел в Речи Посполитой в период его гетманства (1672–1687 гг.). В работе анализируются состав агентов, методы их работы, круг вопросов, интересовавших гетмана и его окружение, а также достоверность свидетельств информаторов. The paper is devoted to considering the question about the role of agents of hetman of Left-Bank Ukraine Ivan Samoylovych in collecting of information about the situation in the Polish-Lithuanian Commonwealth during the period when he was in office (1672-1687). The staff of agents was mostly nonprofessional (townsmen, clerks etc.), only for Cossacks collection of information was a kind of duty of service. Hetman I. Samoylovych also co-operated with Russian central power for gathering of evidences of informants. For hetman’s agents, as a rule, weren’t special procedure of recruitment, but as one may be used oaths and kissing of icons. One of the most commonly used method of working of intelligencers was talk with an informed person. Also they were usually sending Constitutions of General Sejms of the Polish- Lithuanian Commonwealth. The Zaporozhian Host’s hetman and starshyna had much concern with decisions of Sejms of the Polish-Lithuanian Commonwealth because of its determinant role in the power system of Poland. Hetman of Left-Bank Ukraine also interested in information about disposition and transportation of Polish troops, location of kings and other officials of the Polish-Lithuanian Commonwealth, Ukrainian Cossacks on the Polish service, negotiations with Russian representatives etc. The analysis of the believability of the information (there was analyzed some examples of evidences) represented in the article let to conclude, that reliable enough information was being gathered by intelligencers using talk with informed persons, the least reliable information was being collected from rumors. Hetman Ivan Samoylovych and his entourage were examining reliability of information which was being gathered by agents. As a result, the hetman had rather true notion of situation in the Polish-Lithuanian Commonwealth that let him to base his position about Russian-Polish relations for Moscow. The I. Samoylovych’s estimation and his advice in that question were overrated by Moscow officials. The system of the collection and the analysis of agents’ evidences was well-functioned, that was indicated hetman’s showy talents.